Colposcopy Waiting Time for First-diagnosed Abnormal Cervical Cytology Patients: Experiences at Hatyai Hospital - Porntip Tassananutriyakul; Sitchuphong Noothong (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To audit colposcopy waiting time for first-diagnosed abnormal cervical cytology patients at Hatyai Hospital following the standard requirements of the National Health Service Cervical Screening Program (NHSCSP) 2016. Materials and Methods: A retrospective study was carried out for 123 first-diagnosed abnormal cervical cytology patients who attended the colposcopy clinic at Hatyai Hospital, Thailand between October 2017 and May 2018. Statistical analyses were performed.Results: Median colposcopy waiting time at Hatyai Hospital was 11.87 days (interquartile range: 0, 14 days) which achieved the minimum requirements of NHSCSP 2016. However, 94.59% of patients with low grade lesion obtained colposcopy within 6 weeks (minimum requirement ≥ 99%) and 77.55% with high grade lesion obtained colposcopy within 2 weeks (minimum requirement ≥ 93%). The significant factor associated with below standard requirements of waiting time for colposcopy was the default rate.Conclusion: Median colposcopy waiting time at Hatyai Hospital met the standard requirements of NHSCSP 2016 but the proportion of patients who obtained colposcopy within time failed to meet the standard requirements. Improvement in the colposcopy appointment system is essential to rectify this defect.